3-Dimensional electric field distributions of castellated and straight dielectrophoresis electrodes for cell separation - Farahdiana Wan Yunus,; Muhammad Ramdzan Buyong,; Jumril Yunas,; Burhanudin Yeop Majlis,; Azrul Azlan Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper discusses the 3-dimensional (3D) electric field distributions on the surface and across the bulk volume of dielectrophoresis (DEP) electrodes. The importance of obtained high electric field is to ensure that biological particles will be able to separate even at low voltage potentials in order to avoid damage to the biological particles. Two electrodes - straight and castellated, were designed using the COMSOL Multiphysics Software Version 5.2 to compare the surface distribution and volume electric fields along the x, y and z axes. The results showed that castellated electrodes showcased higher electric fields for both the surface and volume factors along all axes. The maximum value of volume electric field results was 3.94×105 V/m along the x-axis, 3.80×105 V/m along the y-axis and 1.65×105 V/m along the z-axis. The maximum value of surface electric fields distributions was 3.39×105 V/m along the x-axis, 2.87×105 V/m along the y-axis and 1.14×105 V/m along the z-axis. Additionally, the uniformity of the electric field lines distribution from the COMSOL Multiphysics also indicated that castellated electrodes have a much higher uniformity. The experimental results showed that the castellated electrodes separated particles much faster at 69 s, as compared to straight electrodes at 112 s. Henceforth, this has proven that castellated electrodes have a high electric field as it separates much faster as compared to straight electrodes.